Construction of Computer Curriculum Resource Platform Based on SSM Framework - Jun, Zhan (2021 IEEE International Conference on Power, Intelligent Computing and Systems (ICPICS), 2021)
The online teaching resource platform of "University Computer" course is designed based on JSP technology, using MySQL database and Tomcat server. SSM framework is adopted in the system development framework, and B/S technology is used to construct the platform resource organization mode. MySQL is used to persist the data in the database, and the online teaching resource platform database is gridded and managed according to the actual needs, and all kinds of data are stored in a standardized and orderly manner. Through further analysis of online teaching resources platform, the functions including online registration and login, browsing of learning resources, teaching video on demand, suggestion and feedback, and collecting resources are designed and implemented, and the platform is used to improve teaching efficiency and teaching methods.